Cultures and materialities of imagination : new drug practices and engagements in a digital world - Sieland, Stephan S. (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"In our current digital era, imagination and the cultural and material conditions by which it is developed are more crucially than ever implicated in the experienced adversities and contradictions of drug use. The technological changes of society underscore the need for rethinking dominant understandings which portray addiction as an immediate and even mindless relation between a person and a substance or behavior, only minimally affected by subjective significance and historical alterations of everyday life. Indeed, from ancient mythology to our modern times drugs have been part of our cultural history. Understandings and practices of their uses have developed through cultural ideas and cultural-material conditions like traditions, rituals and routines. Today, the omnipresence of digital media in everyday life is massively changing and expanding such cultural and material conditions. Digital media equip people with associations between drugs and an incredible abundance of images, ideas, facts, fiction, narratives, plots, soundtracks, characters, and much more, and thereby expanding their imaginable potentials for providing answers to biographical questions. People and potential drug use become connected in novel and labyrinthine ways through digital communities and arrangements of everyday life. And digital media are part of and transform the cultural-material practices in which activities and experiences of intoxication actually take place. In the book, all these details are extensively analyzed empirically based on qualitative data on the lives of a number of young, Danish people who were undergoing treatment for drug-related problems at the time of the research. An underlying premise of the entire work is that addiction may be seen as a more extreme expression of how the technological developments in our contemporary world more generally speaking magnify the contradictory implications of imagination for modern living. Over the recent years, psychological research into the significance of the human capacity to imagine for how people deal with and live their lives has received growing attention. Yet, the complex involvement of imagination in actual living and consequently the theoretical cruxes this engenders continue to amaze and surprise research and researchers. This book also contributes to these theoretical ambitions with a substantial work on the concept of imagination. It primarily suggests that a critical discussion of how imagining is essentially a contradictory process in everyday life and how it is always grounded in the agency of material aspects, ranging anywhere from mundane artifacts over mediated content to advanced technologies, is ultimately what makes the scientific study of imagination relevant to understanding and intervening in the dilemmas and crises of modern life and society"-- Provided by publisher.
Keywords: Youth -- Drug use -- Denmark.; Drug addiction -- Denmark.; Information technology -- Social aspects.; Digital media -- Social aspects.; Psychology -- Psychopathology -- Addiction.; Drugs and alcohol: social aspects.; Addiction and therapy.; elektronické knihy; electronic books